Let c n and d n be integer sequences such that, for all non-negative integers n , we have
( 1 + 2 ) n = c n + d n 2
What is the value of the following expression?
n = 0 ∑ ∞ 7 n c n 2 + 2 d n 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
NICE PROPOSAL :)
Or we could use the fact that c n = 2 ( 1 + 2 ) n + ( 1 − 2 ) n , d n = 2 2 ( 1 + 2 ) n − ( 1 − 2 ) n .
How can you deduct that, Vikram?
Using the binomial theorem.
Problem Loading...
Note Loading...
Set Loading...
Squaring the given equality, we can find that the rational part Q ( n ) of ( 3 + 8 ) n is equal to c n 2 + 2 d n 2 .
Knowing that 3 + 8 is the root of the characteristic polynomial x 2 − 6 x + 1 = 0 , we find the recursive relation Q ( n + 2 ) = 6 Q ( n + 1 ) − Q ( n ) , for Q ( 0 ) = 1 , Q ( 1 ) = 3 . The exact formula for this recursive Q ( n ) can be shown to be
Q ( n ) = 2 ( 3 + 8 ) n + ( 3 − 8 ) n
Notice that ∣ ∣ ∣ 7 3 + 8 ∣ ∣ ∣ , ∣ ∣ ∣ 7 3 − 8 ∣ ∣ ∣ < 1 . Thus we can apply an infinite sum of a geometric progression to get
n = 0 ∑ ∞ 7 n c n 2 + 2 d n 2 = 2 1 ( 1 − 7 3 + 8 1 + 1 − 7 3 − 8 1 ) = 2 7 ( 4 − 8 1 + 4 + 8 1 ) = 2 7 .